Risk Analysis of Occupational Accidents in the Welding Practice Course of the Mechanical Engineering Education Study Program at Universitas Negeri Jakarta Using the Failure Mode and Effects Analysis (FMEA) Method - Ilman Arpi; Pratomo Setyadi; Fajri Darusalam; Waradzi Mustakim (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Occupational accidents may occur in various environments, including higher education laboratories where practical activities involve hazardous equipment and materials. Welding practice is one of the laboratory activities with a high potential for occupational accidents due to exposure to heat, electricity, sparks, fumes, and improper work procedures. Therefore, a systematic risk assessment is necessary to identify potential hazards and develop appropriate control measures. This study aims to identify potential failure modes, evaluate occupational accident risks, and propose risk control strategies in the Welding Practice course of the Mechanical Engineering Education Program at Universitas Negeri Jakarta using the Failure Mode and Effects Analysis (FMEA) method. A descriptive quantitative approach was employed through direct observation, interviews with students, and analysis of course documents, including job sheets and semester learning plans. The results identified nine potential failure modes that may lead to nine types of occupational accidents and thirty possible consequences. Based on the calculated Risk Priority Number (RPN), all identified risks were classified as low-risk categories. Nevertheless, preventive actions remain essential through engineering controls, administrative controls, elimination measures, and the proper use of personal protective equipment (PPE). The findings provide practical recommendations for improving